2022
DOI: 10.3389/fcvm.2022.1002030
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index is associated with quantitative flow ratio in patients with acute ST-elevation myocardial infarction after percutaneous coronary intervention

Abstract: BackgroundThe triglyceride-glucose (TyG) index is a novel marker representing the degree of insulin resistance (IR) and is closely related to cardiovascular diseases. However, the association between the TyG index and vascular function in patients with acute ST-elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI) remains unknown.Materials and methodsThis study was a post hoc analysis of a multicenter, prospective cohort study. In this study, patients with STEMI who underwent P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 49 publications
0
15
0
3
Order By: Relevance
“…Though PH has attracted an increasing amount of attention from clinical physicians and researchers, PH’s clinical characteristics and risk factors in CAD patients who have received PCI treatment have not been widely investigated (19,20,24,25,40). The roles of the TyG index in outcomes of patients who underwent PCI treatment have been partly reported (7,10,41,42). The associations between TyG index and poor prognosis in patients with acute ST-elevation myocardial infarction after PCI have also been indicated in previous studies(7,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though PH has attracted an increasing amount of attention from clinical physicians and researchers, PH’s clinical characteristics and risk factors in CAD patients who have received PCI treatment have not been widely investigated (19,20,24,25,40). The roles of the TyG index in outcomes of patients who underwent PCI treatment have been partly reported (7,10,41,42). The associations between TyG index and poor prognosis in patients with acute ST-elevation myocardial infarction after PCI have also been indicated in previous studies(7,10).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the TyG index in outcomes of patients who underwent PCI treatment have been partly reported (7,10,41,42). The associations between TyG index and poor prognosis in patients with acute ST-elevation myocardial infarction after PCI have also been indicated in previous studies(7,10). However, the potential role of the TyG index as a predictor of PH in CAD patients after PCI treatment has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more studies have found that the TyGI is not only significantly associated with the risk of atherosclerosis, DM, and coronary artery disease, but its elevated levels increase the poor prognosis of CVDs such as in-stent restenosis and atrial fibrillation. 3 The investigation of the relationship between TyGI and coronary slow flow (CSF) could be of great interest in clinical practice, as studies have demonstrated a strong association between IR and CSF, considering IR as an independent risk factor for CSF in patients with IGT. 4,5 Arterial stiffness is one of the earliest types of functional damage that occurs during the vascular aging process, during which arterial elasticity decreases.…”
mentioning
confidence: 99%
“…Furthermore, there is a positive correlation with poor prognosis in patients with acute myocardial infarction when its level exceeds 9.75, which may serve as a threshold for assessing residual coronary ischemia. 3 The TyGI level above 9.75 increased the risk of postpercutaneous coronary intervention quantitative flow ratio ≤ 0.92, which has a poor prognosis. Therefore, TyGI above 9.75 may be used as a threshold for intensive drug therapy to improve coronary ischemia after percutaneous coronary intervention.…”
mentioning
confidence: 99%